PERAN KEPALA SEKOLAH DALAM MENSUKSESKAN PROGRAM LITERASI - Kartini, Dewi; Yuhana, Yuhana (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The background of this research originated from conditions that show literacy ability Indonesian students still relativity low and must be improved. Based on findings in 2016, Puspendik Kemdikbud in the Indonesian National Assessment Program (INAP) test reading skills, the result is 46,83% in the less category, 47,11% in sufficient category, and 6,06% in good category. This problem confirm that the government must implement a specific strategy so that the reading ability of students increasesby following up on the school program which is accommodated in the literacy movement. This researce is descriptive qualitative research type with data collection thechniques in the form of observation, documentation, and interview. This research was conducted at SMP Negeri 1 Indralaya. The results of this study indicate the role of the principal in the success of literacy programs that is a) socialize policies school literacy movement through meeting; b) make a decision letter for the school literacy team; c) provide a reading corner in the class and library; d) always reminding related programs; e) allocate funds for the procurement of books; f) hold competitions; g) requires students to read books every day for 15 minutes before starting class hours.